The Financial Feasibility of Retaining Walls and Winbreaks as Measures of Oil Conservation in Wadi Zabid, Yemen - Al-Sharjabi, Alladeen Mohamad Abdalla (2004)
Wadi Zabid is one of the major agricultural areas of Yemen that faces serious soil erosion (SE) problem caused by water and wind. Some of the farmers in the area have constructed retaining walls (RW) and windbreak (WB) to conserve their farmland soil but many do not. As the SE is becoming serious and soil conservation activity is not progressing, there is a need to reveal the feasibility of soil conservation investment, obstructions to soil conservation and farmers SE perception. Data for this study were collected through questionnaires during the agricultural season of 199912000. The total sample was 264 comprising four groups; i.e., "with" and "without" RW and "with" and "without" WB. The financial benefit cost analysis was the analytical technique and the decision criteria used were the net present value (NPV), internal rate of return (LRR) and benefit cost ratio (BCR). Order logit and logistic models have been applied to reveal farmers characteristics related to the perception of the soil erosion and to the decision of soil conservation, respectively. The study found that the farmer age, number of family working force and number of permanent labourers all have positive relations with the serious perception of soil erosion by water. However, the family size, RW length and farmer experience all have shown negative relations. The model of RW adoption showed that farm-home distance, neighbours complaints and the minor perception of soil erosion by water have positive relation. On the contrary, the size of rented area and farm-market distance both have shown negative relations with RW adoption. In the perception of wind erosion model, the farming period, numbers of WB, presence of demoplots and awareness of soil conservation programmes all have shown positive relations. However, the farmer experience, WB age and neighbours complaints all have shown negative relations with the perception. Nonetheless, the farmer will not plant WB unless he is aged, literate, has more family working force, asked by neighbours and has attended the extension night gatherings. The size of the family and the size of rented farm area have shown negative relations with the adoption of WB measure. In addition, the study found that the investments in RW and WB have been financially feasible. The farmer who has invested in RW has got Yemen Riyals (YRs) 33,652 as NPV (US$l= YRs 150). In term of BCR and IRR the farmer returns are 1.14 and 14 percent, respectively. The farmer who has invested in WB has got YRs 54,190 as NPV and 1.8 and 27 percent as BCR and IRR, respectively. Therefore, as RW and WB proved to be financially feasible then government subsidies are justified and will attract more farmers to conserve their farmland soil. In addition, as the determinants of the perceptions of water and wind erosion are not identical then separate strategies and extension programmes are justified.